Improving Fibrin Hydrogels’ Mechanical Properties, through Addition of Silica or Chitosan-Silica Materials, for Potential Application as Wound Dressings - Natalia Y. Becerra; Luz M. Restrepo; Yessika Galeano; Ana C. Tobón; Luis F. Turizo; Monica Mesa (International Journal of Biomaterials)
Fibrin is a protein-based hydrogel formed during blood coagulation. It can also be produced in vitro from human blood plasma, and it is capable of resisting high deformations. However, after each deformation process, it loses high amounts of water, which subsequently makes it mechanically unstable and, finally, difficult to manipulate. The objective of this work was to overcome the in vitro fibrin mechanical instability. The strategy consists of adding silica or chitosan-silica materials and comparing how the different materials electrokinetic-surface properties affect the achieved improvement. The siliceous materials electrostatic and steric stabilization mechanisms, together with plasma protein adsorption on their surfaces, were corroborated by DLS and ζ-potential measurements before fibrin gelling. These properties avoid phase separation, favoring homogeneous incorporation of the solid into the forming fibrin network. Young’s modulus of modified fibrin hydrogels was evaluated by AFM to quantitatively measure stiffness. It increased 2.5 times with the addition of 4 mg/mL silica. A similar improvement was achieved with only 0.7 mg/mL chitosan-silica, which highlighted the contribution of hydrophilic chitosan chains to fibrinogen crosslinking. Moreover, these chains avoided the fibroblast growth inhibition onto modified fibrin hydrogels 3D culture observed with silica. In conclusion, 0.7 mg/mL chitosan-silica improved the mechanical stability of fibrin hydrogels with low risks of cytotoxicity. This easy-to-manipulate modified fibrin hydrogel makes it suitable as a wound dressing biomaterial.